Genetic diversity and structure of indica rice varieties from two heterotic pools of southern China and IRRI - Xie, Fangming; Guo, Longbiao; Ren, Guangjun; Hu, Peisong; Wang, Feng; Xu, Jianlong; Li, Xinqi; Qiu, Fulin; dela Paz, Madonna Angelita (Cambridge University Press, 2012)
Investigation of genetic diversity and the relationships among varieties and breeding lines is of great importance to facilitate parental selection in the development of inbred and hybrid rice varieties and in the construction of heterotic groups. The technology of single nucleotide polymorphism (SNP) is being advanced for the assessment of population diversity and genetic structures. We characterized 215 widely cultivatedindicarice varieties developed in southern China and at the International Rice Research Institute (IRRI) using IRRI-developed SNP oligonucleotide pooled assay (OPA) to provide grouping information of rice mega-varieties for further heterotic pool study. The results revealed that the Chinese varieties were more divergent than the IRRI varieties. Two major subpopulations were clustered for the varieties using a model-based grouping method. The IRRI varieties were closely grouped and separated clearly from the majority of the Chinese varieties. The Chinese varieties were subclustered into three subgroups, but there was no clear evidence to separate the Chinese varieties into subgroups geographically, indicating a great degree of genetic integration of alleles and shared ancestries among those high-yielding modern varieties.